Bringing Students with Low Agreeableness to Attend Collegiate Sports: A Moderated Mediation Model with Team Identification and Student Involvement - Chanwook Do; Jun-Phil Uhm; Heetae Cho; Hyun-Woo Lee (Journal of Applied Sports Management, 2022)
In a college athletics setting, we investigated a moderated mediation model of the effect of team identification on attendance intention where student involvement was the mediator and agreeableness was the moderator. Results showed that student involvement mediated the relationship between team identification and attendance intention, and agreeableness moderated the effect of student involvement on attendance intention. In particular, the interaction effect by agreeableness indicated how less agreeable students would be more willing to attend games when they are more involved in campus activities. Details of this study, including theoretical and practical implications, research limitations, and future directions, are discussed.
Keywords: team identification; agreeableness; involvement; attendance